2016
DOI: 10.1155/2016/2625870
|View full text |Cite
|
Sign up to set email alerts
|

Process Mapping in a Pediatric Emergency Department to Minimize Missed Urinary Tract Infections

Abstract: Urinary tract infections (UTIs) are common in young children and are seen in emergency departments (EDs) frequently. Left untreated, UTIs can lead to more severe conditions. Our goal was to undertake a quality improvement (QI) initiative to help minimize the number of children with missed UTIs in a newly established tertiary care pediatric emergency department (PED). A retrospective chart review was undertaken to identify missed UTIs in children < 3 years old who presented to a children's hospital's ED with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Studies reported that QI teams gained a more realistic understanding of current practice because PM allowed them to gather knowledge from people directly involved in the process under analysis and provided a visual representation of current or enhanced processes [ 65 , 83 , 96 , 142 ]. The studies show that PM is a tool to break-down the complexity characterizing healthcare, by providing improvement teams with a structured picture of complex processes, using information from process stakeholders holding different roles and perspectives [ 34 , 88 , 90 , 96 , 98 100 , 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported that QI teams gained a more realistic understanding of current practice because PM allowed them to gather knowledge from people directly involved in the process under analysis and provided a visual representation of current or enhanced processes [ 65 , 83 , 96 , 142 ]. The studies show that PM is a tool to break-down the complexity characterizing healthcare, by providing improvement teams with a structured picture of complex processes, using information from process stakeholders holding different roles and perspectives [ 34 , 88 , 90 , 96 , 98 100 , 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most (91%) reported that the map was created to represent "as-is" practice. Four projects [75][76][77][78] reported both "as-is" and "to-be" maps, while 5 describe the "to-be" process. [79][80][81][82][83] For example, in TDABC projects the analysis is focused on process costs and is mainly completed after the "as-is" process map is created.…”
Section: Phasementioning
confidence: 99%